'The government is the cause of the disease and we are stuck with the symptoms': deinstitutionalisation, mental health advocacy and police shootings in 1990s Victoria. Issue 3 (4th May 2017) - Gooding, Piers
Abstract: The deinstitutionalization of mental health services in Australia happened first and most rapidly in the state of Victoria. In the final decades of the 20th Century, a period of immense economic and social policy reform accelerated this shift. Policy change appeared to be guided, at least in part, by ideals of human rights and citizenship. However, these same principles could be undermined in the vacuum of services created by deinstitutionalization and the broader restructuring of the welfare state. One expression of this paradox was a reported increase in violent encounters between police and those in states of distress and mental crises. Another example of paradox was rights-based mental health law, which both increased procedural safeguards for involuntary psychiatric intervention but also perpetuated differential treatment of persons with psychosocial disability on the basis of unfounded beliefs. This article will examine the intersections of policing and mental health policy in order to examine how boundaries of normality and disablement were contested during a transitional period of mental health law and policy.